Culture-negative polymicrobial chronic Q fever prosthetic valve infective endocarditis utilizing 16S ribosomal RNA polymerase chain reaction on explanted valvular tissue. (August 2022) - Garg, Priya; Chan, Stephanie; Peeceeyen, Sheen; Youssef, George; Graves, Stephen R; Sullivan, Richard
Abstract : Q fever is the most commonly reported zoonotic disease in Australia. Endocarditis is one of the most common manifestations of chronic infection. Q fever–related valvular damage may make patients susceptible to other pathogens. We recommend screening for Q fever in endemic areas among patients with endocarditis with valvulopathies. ABSTRACT: Coxiella burnetti is the causative organism of the zoonotic infection Q fever, of which endocarditis is one of the most common manifestations of the chronic form. Polymicrobial endocarditis with Q fever is extremely rare and is yet to be described among an Australasian cohort. Summary: We present the case of a 32-year-old gardener with culture-negative chronic Q fever prosthetic valve endocarditis concomitant with another bacterial pathogen, leading to aortic root abscess formation, requiring a Bentall procedure, extracorporeal membrane oxygenation, and prolonged antimicrobial therapy, with a fatal outcome. Unique to our case, Q fever was identified early, and the second pathogen was only detected on 16S ribosomal RNA (rRNA) polymerase chain reaction of explanted valvular tissue. Given the high risk for morbidity, we recommend that screening for Q fever in endemic areas among patients with infective endocarditis from other etiologies be considered. In addition, this case highlights the role for Q fever vaccination of the at-risk population with underlying valvulopathy. Furthermore, clinicians should be aware of polymicrobial infective endocarditis and suspicious in case of patients with atypical clinical features.